Permasalahan Substansi Hukum Acara Perdata di Peradilan Umum dan Penyelesaiannya - Gunawan, Gunawan; Anggraeni, Happy Yulia; Fitri, Rani Lailatul (Wajah Hukum, 2023)
The substance of the legislation is identified as one of the influential aspects that impact the settlement process of civil matters in the General Court. This particular legal entity encompasses both formal and material aspects of the law. Civil procedural law governs the procedural aspects of case settlement, adhering to formal legal requirements. On the other hand, material law pertains to the substantive legal principles that govern the legal relationship between the parties involved in a dispute. The current state of the Civil Code is incongruent with the prevailing sentiment of public justice, so deviating from the fundamental tenets of national law and dualism. The objective of this study is to gain knowledge and comprehension regarding the issue of legal substance as a contributing factor in the examination of civil cases within the General Court. Furthermore, the aim is to propose a resolution to address the problem of legal substance as a factor impacting the process of examining civil cases in the General Court. The present study constitutes a normative legal research. Based on the outcomes of the discourse, the ensuing deductions may be ascertained: The insufficiency of the existing regulations governing the examination of civil cases in the General Court can be attributed, in part, to the intricate nature of legal substance issues. Consequently, it is imperative to establish a comprehensive legal framework, specifically in the form of the Civil Procedure Code, rather than relying on provisions at a lower hierarchical level, such as Supreme Court Regulations and Supreme Court Circular Letters. Furthermore, in order to garner attention from governmental entities or authorized individuals, such as the House of Representatives of the Republic of Indonesia, the President, and the Supreme Court, it is imperative to seek resolution or settlement in alignment with the enactment of a civil procedure law, specifically a Civil Procedure Code, in accordance with the prescribed legislative procedures.